On The Figure In General And The Body In Particular : Figurative Invention In Cinema - Brenez, Nicole (a New York : Anthem Press, 2023)
A collection of wide-ranging essays written throughout the 1990s, On the Body in General and the Figure in Particular: Figurative Invention in Cinema covers an array of genres and styles to propose an original method of cinematic analysis and interpretation foregrounding film's formal and plastic qualities in all their multifaceted materiality and aesthetics. Brenez reconsiders what a body on film can be and what constitutes a figure in cinema.